The Implementation of Student Facilitator and Explaining Learning Model using Vlog Media to Improve the Creativity and Learning Outcomes of Students in Social Studies Subject at Panakkukang District, Makassar City - Zubaidah Lapi; Muhammad Yunus; Sundari Hamid (Jounal of Primary Education, 2021)
Penelitian ini bertujuan (1) Untuk mengidentifikasi penerapan model pembelajaran students fasilitator and explaining menggunakan media vlog dalam meningkatkan hasil belajar siswa SD pada mata pelajaran IPS di Kecamatan Panakkukang Kota Makassar, dan (2) Untuk mengidentifikasi penerapan model pembelajaran students fasilitator and explaining menggunakan media vlog dalam meningkatkan kreativitas siswa SD pada mata pelajaran IPS di Kecamatan Panakkukang Kota Makassar. Metode penelitian yang adalah Penelitian kuantitatif dengan menggunakan quasi eksperimental design. Populasi dalam penelitian ini adalah siswa SD kelas V di Kecamatan Panakkukang Kota Makassar. Sampel Penelitian ini berjumlah 40 orang siswa yang dibagi menjadi  dua kelompok yaitu kelompok eksperimen dan kolompok kontrol dengan masing kelompok terdiri atas 20 orang siswa SD Inpres Pampang II dan 20 siswa SD Inpres Panaikang II/1 Kota Makassar. Setelah melakukan penelitian, peneliti menyimpulkan bahwa (1) Berdasarkan p-Nilai dari posttest dari kedua kelompok diperoleh hasil lebih rendah dari alfa (0,00<0,05) dan derajat kebebasan adalah 38. Nilai t-test dari kedua kelompok pada posttest dapat disimpulkan ada perbedaan yang signifikan.  Hal ini menunjukkan bahwa Penerapan model pembelajaran students fasilitator and explaining menggunakan media vlog secara signifikan meningkatkan hasil belajar siswa dalam kelompok eksperimen. (2) Penerapan model pembelajaran students fasilitator and explaining menggunakan media vlog meningkatkan kreativitas siswa SD pada mata pelajaran IPS di Kecamatan Panakkukang Kota Makassar. This study aims (1) to identify the implementation of the student facilitator and explaining learning model using the vlog media in improving the learning outcomes of elementary school students in the social studies subject at Panakkukang District, Makassar City, and (2) to identify the implementation of the student facilitator and explaining learning model using the vlog media in increasing the creativity of elementary school students in the social studies subject at Panakkukang District, Makassar City. The research method is quantitative research using a quasi-experimental design. The population in this study were fifth-grade elementary school students in Panakkukang District, Makassar City. The sample of this study was 40 students who were divided into 2 groups, namely the experimental group and the control group, with each group consisting of 20 students from SD Inpres Pampang II and 20 students from SD Inpres Panaikang II/1, Makassar City. After conducting the research, the researcher concluded that (1) Based on the p-value of the posttest of the two groups, the result (0.00) was lower than 0.05 and the degree of freedom was 38. The t-test value of the two groups in the posttest could be concluded that there was a significant difference. This indicates that the alternative hypothesis (H1) is accepted and, of course, the null hypothesis (H0) is rejected. This shows that the implementation of the student facilitator and explaining learning model using vlog media significantly improves student learning outcomes in the experimental group. (2) The implementation of the student facilitator and explaining learning model using vlog media also increases the creativity of elementary school students in the social studies subject in Panakkukang District, Makassar City